2021
DOI: 10.1016/j.celrep.2021.109103
|View full text |Cite
|
Sign up to set email alerts
|

Incoming HIV virion-derived Gag Spacer Peptide 2 (p1) is a target of effective CD8+ T cell antiviral responses

Abstract: Persistence of HIV through integration into host DNA in CD4 + T cells presents a major barrier to virus eradication. Viral integration may be curtailed when CD8 + T cells are triggered to kill infected CD4 + T cells through recognition of histocompatibility leukocyte antigen (HLA) class I-bound peptides derived from incoming virions. However, this has been reported only in individuals with ''beneficial'' HLA alleles that are associated with superior HIV control. Through interrogation of the pre-integration imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the increased CD4+ and CD8+ T cell PFS to HIVconsv Pool 1 + 2, which covers Gag sequences within HIVconsv, suggest that Gag-specific T cell functionality was enhanced by vaccination. We have shown previously that CD8+ T cell targeting of functionally constrained regions within Gag proteins is a major driver of CD8+ T cell antiviral activity 14 , 20 . We surmise, therefore, that the superior CD8+ T cell antiviral effect in the ART + V + V arm was due to a combination of re-focusing, ie.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increased CD4+ and CD8+ T cell PFS to HIVconsv Pool 1 + 2, which covers Gag sequences within HIVconsv, suggest that Gag-specific T cell functionality was enhanced by vaccination. We have shown previously that CD8+ T cell targeting of functionally constrained regions within Gag proteins is a major driver of CD8+ T cell antiviral activity 14 , 20 . We surmise, therefore, that the superior CD8+ T cell antiviral effect in the ART + V + V arm was due to a combination of re-focusing, ie.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these conserved envelope peptides, we also found a gag peptide at AA position 433 that is significantly enriched in NS escape subjects relative to AS escape subjects. This peptide maps to the gag spacer peptide 2 (p1) domain, which is a recently discovered, protective T-cell epitope 28 . Notably, all three of these epitopes (env AA positions 289 and 577, gag AA position 433) in the CSF of PLWH were also identified by Eshleman et al 36 in their VirScan study profiling anti-HIV antibodies in sera from 57 PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that there was a significant enrichment of HIV gag peptides in NS escape (median rpK 41,770, IQR 20,493-54051 rpK) compared to AS escape cases (median rpK 2,953, IQR 673-12848 rpK) (p<0.001) (Figure 3d). The difference in HIV gag protein enrichment in NS escape subjects was largely driven by peptides starting at AA position 433, mapping to the gag spacer peptide 2 (p1) domain, which is a recently discovered, protective T-cell epitope 28 .…”
Section: Virscan Shows Increased Antibody Reactivity To the Gag Prote...mentioning
confidence: 99%